Odpowiedź :
[tex]a)\\\\(2\sqrt[3]{5})^3=2^3*(\sqrt[3]{5})^3=8*5=40\\\\b)\\\\(3\sqrt[3]{2})^3=3^3*(\sqrt[3]{2})^3=27*2=54\\\\c)\\\\(\frac{\sqrt[3]{6}}{3})^3=\frac{(\sqrt[3]{6})^3}{3^3}=\frac{6}{27}=\frac{2}{9}\\\\d)\\\\(\frac{\sqrt[3]{4}}{2})^3=\frac{(\sqrt[3]{4})^3}{2^3}=\frac{4}{8}=\frac{1}{2}[/tex]
[tex]e)\\\\(\frac{3}{\sqrt[3]{15}})^3=\frac{3^3}{(\sqrt[3]{15})^3}=\frac{27}{15}=\frac{9}{5}=1\frac{4}{5}\\\\f)\\\\(\frac{1}{2\sqrt[3]{5}})^3=\frac{1^3}{2^3*(\sqrt[3]{5})^3}=\frac{1}{8*5}=\frac{1}{40}[/tex]